The Cognition Trend of Chinese Traditional Media on Feminism and the Underlying Reason for Existing Negative Reports - Cao Yining (SHS Web of Conferences, 2023)
With the positive development of the media, various mainstream cultures and ideologies have also changed. It is difficult for the two to accommodate. “Feminism”, as a progressive thought, spreads in the media space and has a great impact on the cognition of social equality between men and women. This paper studies and analyses about 200 articles from two traditional Chinese print media, exploring the cognition trend of Chinese traditional media on feminism and the deep reasons for existing negative reports. Conclusions can be drawn that the general attitude of traditional Chinese media to feminism is neutral and positive, while both the traditional dualism of patriarchal society and the reform of social economic structure have influenced the cognition and inclusiveness of traditional media to feminism.